Kecerdasan Majemuk (Multiple Intelligence) - Putri Mariani; Des Fadila Kurnia; Lindra Yarni (KOLONI, 2023)
Multiple intelligences are forms of intelligence that can be possessed by every person. The term multiple intelligence is taken from the meaning of multiple intelligences which was coined by Howard Gardner, a leader of Hardward University's Zero project in 1983. Intelligence also has eight different intelligences and added one more area of ​​intelligence the following year. Intelligence was originally defined in everyday language as the ability to solve practical problems. Intelligence includes three meanings, namely the ability to learn, the overall knowledge acquired and the ability to adapt to new situations and the environment in general. Intelligence was pioneered by a psychologist from Harvard University who stated that every person is intelligent and has a tendency to have intelligence among the eight dimensions of intelligence. Intelligence is not something that is not influenced by culture and genetics.